2022
DOI: 10.3934/publichealth.2022036
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of wellbeing and resilience among refugee mothers and families in Calgary during the COVID-19 pandemic, and the role of participation in HIPPY, a home visiting program

Abstract: <abstract> <p>In order to provide meaningful and effective support to refugees in Canada during the COVID-19 pandemic, as well as during post-pandemic recovery efforts, it is critical to explore the experiences of refugee mothers and families during the pandemic, and to identify sources of resilience that can be leveraged to promote individual and household wellbeing. From November 2020 to June 2021, we conducted in-depth interviews with mothers from refugee backgrounds (n = 28) who resettled in Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
(79 reference statements)
1
2
0
Order By: Relevance
“…This finding is linked to hopes for their children’s future and the potential for prosperity. Consistent with other research on the effects of Covid-19 on newcomers and refugee mothers, our findings show that Syrian mothers experienced a negative impact on their health and well-being [ 33 , 34 ]. These negative affects were frequently related to social isolation and an increase in their gendered, domestic care responsibilities.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is linked to hopes for their children’s future and the potential for prosperity. Consistent with other research on the effects of Covid-19 on newcomers and refugee mothers, our findings show that Syrian mothers experienced a negative impact on their health and well-being [ 33 , 34 ]. These negative affects were frequently related to social isolation and an increase in their gendered, domestic care responsibilities.…”
Section: Discussionsupporting
confidence: 91%
“…The most difficult thing is I can’t give her more difficulties on her shoulder , yeah , that’s enough for her . So , I just get silent , I don’t tell them even if I want to tel l. [ 34 ]…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported a variety of coping strategies, such as establishing harmonious interpersonal relationships, building a good community environment, and creating a good climate of public opinion ( 18 ). These external pillars have played an instrumental role in surmounting adversities amidst the pandemic ( 19 ). In addition, personal factors such as a positive mindset, optimism, and inner drive are also important, with resilience being one of the individual inner drives that have been particularly highlighted in previous reports ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus Disease 2019 (COVID- 19) has left an indelible mark on community life, healthcare, and education (1,2). Governments worldwide have responded with myriad measures, ranging from city lockdowns to social isolation, quarantines for infected populations, and home isolation (3).…”
Section: Introductionmentioning
confidence: 99%